Willy Loman’s Superiority Complex Reflected in Arthur Miller’s Death of a Salesman - Ellen Feliana; Norita Prasetya Wardhani; Yanuaresti Kusuma Wardhani; Hardono Hardono (J-Lalite: Journal of English Studies, 2023)
The focus of the study is to describe the characteristics of the superiority complex and explain the causes of the superiority complex reflected by Willy Loman in Arthur Miller’s Death of a Salesman using the superiority complex theory proposed by Adler. This study used a descriptive qualitative method to analyze the problems. It employs qualitative research to categorize the evidence in a frequency table. The study shows that Willy exhibits all of the characteristics of aggressiveness expected of the self-accusative type. The most dominant traits Willy suffers from are exaggerated claims about himself and hostility toward the depreciation type. He also undergoes all of the causes of the superiority complex, such as Pampered Lifestyle and Feeling Neglected. So, from the social perspective, The death of Willy Loman reflects the heavy burden of his life in achieving his dream to be a successful parent who educates his sons. His obsession causes him to commit suicide, and he develops a superiority complex to sacrifice for his family.